153-2x=43x+23

Simple and best practice solution for 153-2x=43x+23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 153-2x=43x+23 equation:


Simplifying
153 + -2x = 43x + 23

Reorder the terms:
153 + -2x = 23 + 43x

Solving
153 + -2x = 23 + 43x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-43x' to each side of the equation.
153 + -2x + -43x = 23 + 43x + -43x

Combine like terms: -2x + -43x = -45x
153 + -45x = 23 + 43x + -43x

Combine like terms: 43x + -43x = 0
153 + -45x = 23 + 0
153 + -45x = 23

Add '-153' to each side of the equation.
153 + -153 + -45x = 23 + -153

Combine like terms: 153 + -153 = 0
0 + -45x = 23 + -153
-45x = 23 + -153

Combine like terms: 23 + -153 = -130
-45x = -130

Divide each side by '-45'.
x = 2.888888889

Simplifying
x = 2.888888889

See similar equations:

| 2x+7=-89-10x | | 14-10x=124-45x | | 48=x(x+8) | | 7v^2-27v-4=0 | | 4x+37=14x-53 | | 5m^2+6m-8=0 | | x*25=50 | | 50x^2+50x-1000=0 | | .1x+x=125000 | | 2x+3(x-2)=4 | | 2y-5=15 | | (x-4)(x+5)=0 | | 1.1=4y+16.7 | | .40*55=x | | 5(x-3)=8-3x | | 6x^3-5x^2-4x+3= | | 6x^3-5x^2-4x+3byx-1= | | x^2-11x-9=0 | | x^2-4x+2=-2 | | 7x-3=12+2x | | 1(1x+12)= | | d-15=3d-3 | | 48-7d=-8+d | | 18d+1=17d+6 | | 16-d=d+4 | | d-4=2d-14 | | 44-3c=11 | | 4(c-2)=0 | | 2c+6=12 | | 6b=-2 | | 15-b=20 | | -b+4=1 |

Equations solver categories